Sensing Behaviour Investigation of Amperometric Electrochemical NH3 Sensor: Optimization of Lanthanum Gallate Based Electrolyte Composition. Issue 11 (23rd July 2020) - Sharan, R.; Roy, Mainak; Dutta, Atanu
Abstract : To delineate the ammonia sensing mechanism by amperometric sensors a series of lanthanum gallate based electrolytes having nominal compositions of La0.8 Sr0.2 Ga0.8 Mg0.2−x Nix O3 (0 ≤ x ≤ 0.2) and La0.8 Sr0.2 Ga1−y Fey O3 (0.01 ≤ y ≤ 0.1) were prepared by solution combustion technique. Phase purity of electrolyte pellets was achieved by high temperature sintering process. Aforementioned electrolyte compositions were investigated for NH3 sensing performance in the temperature range of 300 °C–550 °C. Exposing the sensors alternately to the base gas (5% O2 + N2 ) and 3–40 ppm NH3 in base gas. Effect of oxygen pumping current on sensing mechanism was studied. The electrolytes with 10 mol% Ni and 5 mol% Fe doping showed the highest sensitivity of 35 and 43 μ A decade −1 at 400 °C and 450 °C respectively. Conductivity measurements showed conductivity of 526 × 10 −5 at 400 °C and 1080 × 10 −5 S cm −1 at 450 °C for La0.8 Sr0.2 Ga0.8 Mg0.1 Ni0.1 O3 and La0.8 Sr0.2 Ga0.95 Fe0.05 O3 respectively. A correlation between conductivity and gas sensing was established. Finally, a mechanism based on the hypothesis of defect cluster formation due to aliovalent doping that enhanced conductivity coupled with oxygen pumping current was proposed.